The Economics of Epidemiology - Tassier, Troy.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book presents a basic introduction to epidemiology from the perspective of economics, using economic modeling to better understand and describe how infectious disease spreads. Three main elements are introduced: epidemiology, social network analysis, and the economics needed to model the behavior of individuals in the presence of infectious disease. The book aims to provide a starting point for discussion between medical professionals, social scientists and public health officials, the three groups interested in the spread of disease.
Preface -- Introduction -- Part I: Epidemic Modeling -- Part II: Merging Economics and Epidemiology -- Part III: An Introduction to Social Interactions -- Part IV: Strategic Decision Making.
Keywords: Economics; Public health; Epidemiology; Economics/Management Science; Health Economics; Epidemiology; Public Health